The Strategies Dealing with Non-Equivalence Problem in The English-Indonesia Version of Song Lyric Lead the Way - Betari Irma Ghasani (Universitas Ngudi Waluyo, 2021)
As a feature of translation, the concept of equivalence is a crucial issue which have to be considered by the translator. Equivalence is a term proposed by Baker (1992) for gaining the equal meaning between the source text and the target text. In translating the source text, some non-equivalence problems happen since several source language has unequal meaning with the target language. Objective of the Paper. This paper aims to identify, describe, and explain some problems of non-equivalence problem at word level and strategies dealing with it. Method. By using Baker’s theory (1992), the song lyric of both English and Indonesian version entitled Lead the Way (sung by Jhené Aiko) and Kita Bisa (sung by Via Vallen) are analyzed. Findings. The findings show that translation by omission is highly applied in translating the lyric followed by a varied occurrence of other strategies. Conclusion. The variation of the strategies is used in order to make a “singable” song. Finally, this paper provides suggestions that a study of the translation of song lyrics combining translation theory and interpersonal meaning of SFL for giving a better understanding is needed to be done for giving a broader understanding towards the text.